A study of conservation and preservation on historical landscape garden as a public park - 384389 Chua, Nee Sheng (Skudai : Universiti Teknologi Malaysia, 2006)
Topical Study (Sarjana Muda Senibina Landskap) - Universiti Teknologi Malaysia, 2006